2018
DOI: 10.1002/jmv.25222
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection and phylogenetic analysis of human parechovirus in individuals with acute diarrhea and healthy controls in Guangzhou, China

Abstract: Human parechoviruses (HPeVs) are prevalent in young children; however, their effects are incompletely understood. We investigated the prevalence, genotype distribution, and phylogeny of HPeVs in individuals with diarrhea (n = 430) and healthy controls (n = 93) by the analysis of stool specimens collected from July 2013 to December 2014; 51 (11.86%) and 6 (6.45%) specimens were HPeV positive, respectively. HPeV1A occurred in 28 (6.51%) and 6 (6.45%) individuals with diarrhea and controls, respectively, whereas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 66 publications
(145 reference statements)
0
6
0
Order By: Relevance
“…The largest study in a cross‐sectional setting investigated 2381 gastroenteritis cases in Japan, 53 while the smallest one covered 50 healthy children in Nigeria 25 . The remaining eight case‐control studies consisted of 4624 paediatric children with gastroenteritis and 1469 healthy controls 68–75 . In the present systematic review and meta‐analysis, more studies were carried out in China ( n = 9), Japan ( n = 5), and Thailand ( n = 4) than other countries; a majority of studies ( n = 31) provided information on the genotype distribution of PeV‐As; 16 of the 41 studies described the case definition of gastroenteritis; most of these data either represented children younger than 5 years or less than 15 years of age.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The largest study in a cross‐sectional setting investigated 2381 gastroenteritis cases in Japan, 53 while the smallest one covered 50 healthy children in Nigeria 25 . The remaining eight case‐control studies consisted of 4624 paediatric children with gastroenteritis and 1469 healthy controls 68–75 . In the present systematic review and meta‐analysis, more studies were carried out in China ( n = 9), Japan ( n = 5), and Thailand ( n = 4) than other countries; a majority of studies ( n = 31) provided information on the genotype distribution of PeV‐As; 16 of the 41 studies described the case definition of gastroenteritis; most of these data either represented children younger than 5 years or less than 15 years of age.…”
Section: Resultsmentioning
confidence: 99%
“…Among the included case‐control studies, only one observed a significantly positive association of PeV‐A infection with gastroenteritis risk in children 74 . Three studies reported a positive correlation between PeV‐A and gastroenteritis in children without statistical significance 68,69,72 . We conducted the second analysis on data from case‐control studies to investigate the relationship between PeV‐A infection and the risk of gastroenteritis in young people aged less than 18 years, with the pooled OR value of 1.079 (95% CI: 0.730–1.597) between the case and control groups (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…On specific genotype distribution, reports from Europe and the USA indicated a higher prevalence of PeV‐A1 and PeV‐A3, followed by 4 and 2, while genotypes 7 to 19 were least reported 18,20,26,32,50‐58 . Similar PeV‐1, 3, and 4 are the most prevalent in Asia, with higher diversity from China, India, and Pakistan 27,59‐66 . In Africa, there is a high prevalence of PeV‐A1, 2, and 3, with evidence suggesting the circulation of many genotypes in the region 10,16,25,31,67‐69 …”
Section: Epidemiology and Pathogenesismentioning
confidence: 99%
“…18,20,26,32,[50][51][52][53][54][55][56][57][58] Similar PeV-1, 3, and 4 are the most prevalent in Asia, with higher diversity from China, India, and Pakistan. 27,[59][60][61][62][63][64][65][66] In Africa, there is a high prevalence of PeV-A1, 2, and 3, with evidence suggesting the circulation of many genotypes in the region. 10,16,25,31,[67][68][69] Moreover, most of what is known about HPeVs comes from pediatric infections.…”
Section: Introductionmentioning
confidence: 99%
“…Another genus of picornaviridae named human parechovirus (HPeVs) has been found to be implicated in acute gastroenteritis (18). The role of EVs in acute diarrhea in children has not been yet investigated in Iran.…”
Section: Introductionmentioning
confidence: 99%